2020
DOI: 10.3390/molecules25112602
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Based Molecules as Potential New Antiparasitic Drugs

Abstract: Neglected tropical diseases such as Chagas disease and leishmaniasis affect millions of people around the world. Both diseases affect various parts of the globe and drugs traditionally used in therapy against these diseases have limitations, especially with regard to low efficacy and high toxicity. In this context, the class of bisphosphonate-based compounds has made significant advances regarding the chemical synthesis process as well as the pharmacological properties attributed to these compounds. Among this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 132 publications
(193 reference statements)
0
8
0
Order By: Relevance
“…Although bisphosphonates are the first-line treatment for many patients with osteoporosis, few studies have been performed to determine any substantial link between the complex nature and function of the gut microbiome and bisphosphonate use. However, in a recent study, bisphosphonates were shown to have potential antiparasitic activity through interaction with the mevalonate (MVA) pathway, one of two primary pathways for synthesizing isoprenoids [162]. Until recently, it was thought that the MVA pathway was rarely used in bacteria; however, in a 2011 study on the genetic origins of the MVA pathway, several species of the phyla Bacteroidetes and Firmicutes, predominant phyla in the gut microbiome [163], were identified as having enzymes of the pathway [164].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Although bisphosphonates are the first-line treatment for many patients with osteoporosis, few studies have been performed to determine any substantial link between the complex nature and function of the gut microbiome and bisphosphonate use. However, in a recent study, bisphosphonates were shown to have potential antiparasitic activity through interaction with the mevalonate (MVA) pathway, one of two primary pathways for synthesizing isoprenoids [162]. Until recently, it was thought that the MVA pathway was rarely used in bacteria; however, in a 2011 study on the genetic origins of the MVA pathway, several species of the phyla Bacteroidetes and Firmicutes, predominant phyla in the gut microbiome [163], were identified as having enzymes of the pathway [164].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…25 The treatment of pamidronate (a bisphosphonate drug) on L. mexicana amazonensis was found effective by Rodriguez et al 26 Detailed reviews on the use of bisphosphonate-based compounds as antiparasitic drugs can be found elsewhere. 27 Notably, supplementation of vitamin E promoted the multiplication of L. donovani in experimental hamsters. However, inhibitors targeting other enzymes of this pathway have not been studied and remain a potential research area.…”
Section: Inhibitors Of Tocopherol Pathwaymentioning
confidence: 99%
“…The treatment of pamidronate (a bisphosphonate drug) on L. mexicana amazonensis was found effective by Rodriguez et al Detailed reviews on the use of bisphosphonate-based compounds as antiparasitic drugs can be found elsewhere . Notably, supplementation of vitamin E promoted the multiplication of L.…”
Section: Inhibitors Of Tocopherol Pathway Enzymesmentioning
confidence: 99%
“…One of the highlighted applications of phosphonates has been reported in the COVID-19 pandemic ( Jockusch et al, 2020 ). Among the various phosphonates and bisphosphonates, hydroxy- and amino-phosphonates and -bisphosphonates are of interest as effective in medicinal and industrial chemistry ( Ebetino et al, 2022 ) ( Santos et al, 2020 ). For example, hydroxy bisphosphonates are well-known bone disease drug candidates, and there are eight clinical hydroxy bisphosphonate drugs that have been introduced for bone diseases due to their high tendency to bind hydroxyapatite, the bone mineral compounds.…”
Section: Introductionmentioning
confidence: 99%